A Semiotic Analysis of Verbal and Visual Signs in Scarlett’s Advertisement “Get Ready to Meet Song Joong Ki’s New Love” - haidah situmorang; Juliva Banjarnahor; Lidia Daeli; Tantri Aurelia Gulo; Rina Octavia Simarmata (Merwin Publisher, 2025)
This research is entitled An Analysis of Verbal and Visual Signs in Scarlett’s Advertisement “Get ready to meet Song Joong Ki’s new love”. The purpose of this study is to analyze the verbal and visual signs found in the advertisement and to uncover the meanings behind those signs. This research applies Roland Barthes’ semiotic theory (1957), which consists of three levels of signification: denotation, connotation, and myth. The method used in this research is descriptive qualitative. The data were collected from the official Scarlett advertisement featuring Song Joong Ki, which was published on various digital platforms. The results of the study showed that there were four verbal signs, which consisted of four written verbal elements one audiovisual verbal element: Song Joong Ki’s spoken words in the video, Each of these verbal signs carries both denotative and connotative meanings that contribute to the advertisement’s persuasive power. The analysis shows that the advertisement uses both verbal and visual signs to deliver its message persuasively. The verbal signs, especially the slogan ―Get ready to meet Song Joong Ki’s new love,‖ are loaded with connotative meanings that create curiosity and emotional connection with the audience. Meanwhile, the visual signs—including color schemes (dominated by soft pink and white), product layout, Song Joong Ki’s gestures and facial expressions—complement the verbal messages and reinforce Scarlett’s brand identity. The study also reveals the presence of myths related to beauty standards, the influential power of celebrities, and the idealization of romantic love. Through this advertisement, Scarlett constructs a narrative that beauty, brightness, and love are attainable through the use of their products